Zoned Pyroxenes as Prospectivity Indicators for Magmatic Ni-Cu Sulfide Mineralization - Schoneveld, Louise; Barnes, Stephen J.; Makkonen, Hannu V.; Le Vaillant, Margaux; Paterson, David J.; Taranovic, Valentina; Wang, Kai-Yuan; Mao, Ya-Jing (Frontiers in Earth Science, 2020)
Small intrusions dominated by olivine- and pyroxene-rich cumulates are well known to be favourable hosts to magmatic Ni-Cu-(Platinum Group Element - PGE) sulfide mineralization. Such intrusions are common in a variety of settings around the world, but only a very small proportion contain economically exploitable sulfides; these tend to be of conduit or chonolith style. If prospectivity could be discriminated from sparse sampling at early exploration stages, then the discovery rate for deposits of this type could be improved. To this end, a number of pyroxene-bearing samples from small intrusions containing magmatic sulphide deposits have been investigated including the Noril’sk-Talnakh camp in Siberia, the Kotalahti nickel belt in Finland, Ntaka Hill in Tanzania, Nova-Bollinger in the Albany-Fraser Orogen of Australia, Savannah in the Halls Creek Orogen of Australia, Jinchuan in central China, Xiarihamu in Tibet and Huangshanxi in the east Tianshan Ni province of NW China. To compare, samples from unmineralised intrusions in four of these regions were also investigated along with four mafic intrusions from other localities that are not associated with any known economic sulfide mineralisation. Using fine-scale (<5 μm/pixel) chemical imaging on the Australian Synchrotron, complex zoning in chromium was found in cumulate and poikilitic pyroxenes within the strongly mineralised intrusions. The zoning patterns can be separated into three distinct types: 1) abrupt zoning: a single change in trace element concentration with a sharp boundary; 2) sector zoning: hourglass style zonation; and 3) oscillatory zoning: small scale oscillations that are usually cyclic. Zoning of all three types can be present in a single grain. The presence of cumulus orthopyroxene with a combination of abrupt zoning, sector zoning and resorbed olivine inclusions has so far only been detected in mineralised intrusions. This combination of zoning patterns is postulated to be an indication of high magma flux and fluctuating cooling rates that accompany wall rock assimilation in dynamic conduits where sulphide liquid forms and accumulates. The distinctive zoning patterns reported here can, in many cases, be easily imaged using desktop microbeam XRF mapping techniques and may provide a useful fertility indicator for the exploration of new magmatic Ni-Cu-(PGE) deposits.